Mixtures of herbicides against weeds in annual cotton - Azevêdo, Demóstenes Marcos Pedrosa de; Beltrão, Napoleão Esberard de Macêdo; Nóbrega, Laudemiro Baldoíno da (Pesquisa Agropecuaria Brasileira, 2014)
In order to determine the efficiency of herbicide mixtures against annual weeds and their phytotoxic effects in cotton (Gossypium hirsutum L. r. latifolium Hutch.) a field trial was placed in 1979 at Surubim, State of Pernambuco, Brazil. The results showed that the mixtures test [trifluralin ppi (pre planting incorporated) + diuron pre (pre-emergence); trifluralin ppi + fluometuron pre; pendimenthalin + diuron pre; pendimethalin + fluometuron pre; alachlor + diuron pre; alachlor + fluometuron pre] showed to be selective to cotton plants, effective against annual weeds for a period of approximately 60 days, and none of the herbicide mixtures affected the yield and fiber qualities of cotton. The predominant weed species were: Ageratum conyzoides L, Boerhavia diffusa L., Acanthospermum hispidum DC., Cenchrus echinatus L., Digitaria sanguinalis Willd. and Rhynchelitrum roseum (Ness) Stapf et Hubb.